INQUIRY-BASED LEARNING FOR STUDENTS’ SPEAKING SKILL IMPROVEMENT: VOICES AND REALITIES FROM THE GROUND - Irham Irham; Septia Dwi Jayanti (Journal of English for Academic and Specific Purposes, 2020)
To improve the students’ speaking proficiency is one of key focuses in EFL teaching. However, most students at intensive English (IE) program administered by the Language Center in the University of MI (pseudonym), one of state universities in Malang, still encounter several major problems in speaking English such as that they do not know what to say, they frequently get stuck, or they have such high levels of anxiety. These contribute much to the students’ limited speaking competence. Therefore, the current paper examines teaching and learning practice in IE program which focuses on speaking and listening skills and aims at formulating the appropriate implementation of inquiry-based learning to improve the students’ speaking skills. The data were collected through oral presentation test, questionnaire, field-notes, and interview. The criteria of success are that (1) every student gets a minimum score of 70, and (2) 75% of the class has positive attitude toward the strategy. The findings of the study revealed that the strategy could indeed improve the students’ speaking skill. In addition, it could increase their self-esteem as well as encouraged them to involve more in the learning processes. Such values might be gained when the strategy takes the steps which facilitate the students to: (1) respond several guiding questions which stimulate investigation; (2) investigate some texts, real objects, pictures, or persons to gather the required information; (3) create new ideas by discussing the information with peers; (4) present the ideas in front of the class; and (5) reflect on their own performance.